CCL5–Glutamate Cross-Talk in Astrocyte-Neuron Communication in Multiple Sclerosis - Pittaluga, Anna (Frontiers in Immunology, 2017)
The immune system (IS) and the central nervous system (CNS) are functionally coupled and a large number of endogenous molecules (i.e. the chemokines for the IS and the classic neurotransmitters for the CNS) are shared in common between the two systems. These interactions are key elements for the elucidation of the pathogenesis of central inflammatory diseases. In recent years evidence have been provided supporting the role of chemokines as modulators of central neurotransmission. It is the case of the chemokines CCL2 and CXCL12 that control pre and / or postsynaptically the chemical transmission. This article aims to review the functional cross-talk linking another endogenous proinflammatory factor released by glial cells, i.e. the chemokine Regulated upon Activation Normal T cell Expressed and Secreted, (RANTES, CCL5) and the principal neurotransmitter in CNS (i.e. glutamate) in physiological and pathological conditions. In particular, the review will discuss preclinical data concerning the role of CCL5 as a modulator of central glutamatergic transmission in healthy and demyelinating disorders. The CCL5-mediated control of glutamate release at chemical synapses could be relevant either to the onset of psychiatric symptoms that often accompany the development of MS, but also it might indirectly give a rationale for the progression of inflammation and demyelination. The impact of disease modifying therapies for the cure of MS on the endogenous availability of CCL5 in CNS will be also summarized. We apologize in advance for omission in our coverage of the existing literature.